Deciphering the Pyroptosis-Related Prognostic Signature and Immune Cell Infiltration Characteristics of Colon Cancer - Wei, Ran; Li, Shuofeng; Yu, Guanhua; Guan, Xu; Liu, Hengchang; Quan, Jichuan; Jiang, Zheng; Wang, Xishan (Frontiers in Genetics, 2021)
Background: Colon cancer (CC) remains one of the common malignant tumors with a poor prognosis. Pyroptosis, an inflammatory form form of programmed cell death, could regulated the tumor development. Potential roles of pyroptosis-related regulators (PRRs) in CC immune microenvironment regulation remain unknown. Methods: We comprehensively evaluated the three pyroptosis-related molecular patterns of 1334 CC samples based on 27 PRRs, and systematically correlated these molecular patterns with immune microenvironment regulation characteristics. The pyroptosis-related genes were identified with WGCNA, which was used to establish risk assessment model for predicting prognosis with Lasso-penalized Cox regression analysis. Results: The CC patients were subtyped in three distinct pyroptosis-related molecular patterns. These pyroptosis-related patterns present feature different clinical outcomes and immune microenvironment cell-infiltrating characteristics. The pyroptosis-related eight signatures model, named “PRM-scores”, were established, and used to predict the prognosis of CC patients with medium-to-high accuracy. The greater inflammatory cell infiltration was observed in low PRM-scores with potential response of immunotherapy. Conclusions: This study suggested the significant role of PRRs in regulation of tumor immune microenvironment and tumor development. Evaluating the pyroptosis-related patterns and model could contribute to promote the understanding of immune microenvironment infiltration characterization and provide theoretical basis for future research targeting pyroptosis